Training on Digital Teaching Aids for Early Childhood Education for the Diploma Association of Early Childhood Education at Universiti Sultan Idris, Malaysia - Jhoni Warmansyah; Komalasari, Elis; Fitriani, Wahidah; Permatasari, Dola; Ismandela, Afriyane; Fatma Nabila, Dinda; Binti Daud, Norrulkamari (Jurnal Pengabdian Masyarakat Ilmu Pendidikan, 2024)
The aim of this International Community Service endeavor is to offer training to future educators of early childhood on creating basic storybooks for instructional use in preschool units. The focus lies on utilizing the Canva digital platform for crafting teaching materials. The target recipients of this service are 50 students affiliated with the Diploma Association of Early Childhood Education (PDPAKK) at UPSI, Malaysia. The methodology employed is Participatory Action Research (PAR). After the training was completed, an assessment carried out by the community service team revealed that the training participants responded positively to the training session. The enthusiasm of the participants was seen by active participation in training activities. The success of the training was proven by the participants' enthusiasm and active participation in activities such as asking, discussing, and answering questions from the presenters.